Dietary sources of vitamin B-12 and their association with plasma vitamin B-12 concentrations in the general population: the Hordaland Homocysteine Study. - Vogiatzoglou, A; Smith, A; Nurk, E; Berstad, P; Drevon, C; Ueland, P; Vollset, SE; Tell, G; Refsum, H (2009)
BACKGROUND: Limited information is available on the association between vitamin B-12 status and intake from different dietary sources. OBJECTIVE: We investigated the relation of dietary intake of different food items with plasma vitamin B-12 concentrations in the general population. DESIGN: A cross-sectional, population-based study of 5937 subjects in 2 age groups (47-49 and 71-74 y) from the Hordaland Homocysteine Study in Norway was conducted by using a food-frequency questionnaire and measurements of plasma vitamin B-12 concentrations. RESULTS: A significant difference in plasma vitamin B-12 concentrations was observed with increasing total vitamin B-12 intake. A plateau was reached at an intake of approximately 10 microg/d. Plasma vitamin B-12 was associated with intakes of increasing amounts of vitamin B-12 from dairy products or fish (P for trend <0.001 for both) but not with intakes of vitamin B-12 from meat or eggs. For the same content of vitamin B-12, intake from dairy products led to the greatest increase in plasma vitamin B-12. Total intake of vitamin B-12, particularly from milk and fish, decreased the risk of vitamin B-12 concentrations <200 pmol/L and impaired vitamin B-12 function (vitamin B-12 <200 pmol/L and methylmalonic acid >0.27 micromol/L) in the total group and in 71-74-y-old subjects. CONCLUSIONS: Dietary intake of dairy products and fish are significant contributors to plasma vitamin B-12 and may improve plasma vitamin B-12 status. Vitamin B-12 appears to be more bioavailable from dairy products; guidelines for improving vitamin B-12 status should take this into consideration.